Manufacturing And Installing Alcohol Barriers In Rt 20 Rw 01 Pematang Governor: Improve Identification And Order - Rahmadani, Emilda; Adila, Novinia; Putra, Septa Adiguna; Afriani, Melati; Ilahi, Pandu Nur Akbar; Tambunan, Dennis Rydarto; Susanti, Neri; Fitriano, Yun (Jurnal Pengabdian Mandiri, 2025)
This community service program aimed to design and install gang signs in RT 20 RW 01, Kelurahan Pematang Gubernur, Kota Bengkulu, to improve location identification and neighborhood order. The participatory approach involved collaboration between KKN-T students and local residents through site surveys, design, fabrication, and installation of six gang signs. Data collection was conducted through observation and informal interviews with residents to assess the impact of the signs. The results showed that the installed gang signs significantly facilitated navigation for residents and visitors, enhanced community safety, and fostered a sense of responsibility among the community members. Suggestions for future programs include incorporating local cultural elements into the design and ensuring regular maintenance to sustain the benefits. This program demonstrates the importance of community involvement in environmental improvements and the practical application of student knowledge in real-world settings.